The value of sport : insights - Stewart, Bob, 1946-; Smith, Aaron, 1972- (Sport business insights., 2025)
"This concise and thought-provoking book examines the myths and realities surrounding the wider value of sport. It asks a fundamental question: what is it about sport that leads to grand claims about its supposed capacity to do so many good things for society? Presenting fresh thinking on an important topic, this book is essential reading for anybody working in sport policy, sport governance, sport management or wider public policy"--